2020
DOI: 10.1007/s00521-019-04697-6
|View full text |Cite
|
Sign up to set email alerts
|

U-COSFIRE filters for vessel tortuosity quantification with application to automated diagnosis of retinopathy of prematurity

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Literature features a large volume of research works on eye imaging. When compared to retinabased blood vessel segmentation studies [6][7][8][9], the amount of research publications on tear film imaging is very less. The research contributions [5,10,11] published by VARPA group are the only reference available for this study.…”
Section: Related Workmentioning
confidence: 99%
“…Literature features a large volume of research works on eye imaging. When compared to retinabased blood vessel segmentation studies [6][7][8][9], the amount of research publications on tear film imaging is very less. The research contributions [5,10,11] published by VARPA group are the only reference available for this study.…”
Section: Related Workmentioning
confidence: 99%
“…1c, respectively. A curved receptive field was configured in [35], to detect high curvature points of the retinal vessel tree. In [40,42], the authors demonstrated that a bank of B-COSFIRE filters, configured to delineate lines of different thickness, can be used as feature extractors and combined with a classifier to perform complex decisions.…”
Section: Edge and Line Detectionmentioning
confidence: 99%
“…1c, respectively. A curved receptive field was configured in [35], to detect high curvature points of the retinal vessel tree. In [42,40], the authors demonstrated that a bank of B-COSFIRE filters, configured to delineate lines of different thickness, can be used as feature extractors and combined with a classifier to perform complex decisions.…”
Section: Edge and Line Detectionmentioning
confidence: 99%